A BRIEF INFORMATION ON TUNA POLE-AND-LINE LANDINGS AND FISHING EFFORTS IN LARANTUKA, FLORES TIMUR DISTRICT, NUSA TENGGARA TIMUR PROVINCE, INDONESIA - Lantun Paradhita Dewanti; Hendra Yusran Siry; Alexander Muhammad Akbar Khan (Indonesian Fisheries Research Journal, 2021)
This research examines tuna pole-and-line landings data by focusing on trend and effort levels in Larantuka, Flores Timur District, Nusa Tenggara Timur Province, Indonesia. The analyzed fisheries data indicate trends that might be useful for monitoring and management purposes. The research data used were from the landings, number of trips, and fishing gear data on tuna pole-and-line from 2005 to 2014 provided by local fisheries authority. Data was also sourced from previous publications and field surveys. This research analyzes data on tuna pole-and-line fishery trends, relationships between landings, number of trips, and fishing gears used. Overall, the data on tuna landings from 2005-2014 increased whilst on the contrary there was a decrease in the numbers of trips and fishing gears used. The relationship between landings to trips (slope =               -0.0087; p-value = 0.7639) and gears (slope = 8.1285; p-value = 0.2715) can be interpreted as being a unit increase in number of trips, which tended to be linked with a decrease of 0.0087 tons in landings. In contrast, a unit increase in gears tended to be associated with an increase of 8.1285 tons in landings.The research did not show statistically significant relationships among      landings, numbers of both trips, and fishing gears.